2022
DOI: 10.1186/s12864-022-08491-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and functional bioinformatics analysis of genes associated with Crohn’s disease identify more than 120 related genes

Abstract: Background Crohn’s disease is one of the two categories of inflammatory bowel diseases that affect the gastrointestinal tract. The heritability estimate has been reported to be 0.75. Several genes linked to Crohn’s disease risk have been identified using a plethora of strategies such as linkage-based studies, candidate gene association studies, and lately through genome-wide association studies (GWAS). Nevertheless, to our knowledge, a compendium of all the genes that have been associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…[ SNX20 ]: SNX20 interacts with the cytoplasmic domain of PSGL1 and cycles PSGL1 into endosomes. SNX20 gene was added manually as one of the 126 significant genes associated with CD in a systematic review and functional analysis of a gene set potentially related to CD [46]. Besides, to increases the power of GWAS studies, Abegaz et al studied the impact of confounding in gene–gene interaction (epistasis) detection.…”
Section: Resultsmentioning
confidence: 99%
“…[ SNX20 ]: SNX20 interacts with the cytoplasmic domain of PSGL1 and cycles PSGL1 into endosomes. SNX20 gene was added manually as one of the 126 significant genes associated with CD in a systematic review and functional analysis of a gene set potentially related to CD [46]. Besides, to increases the power of GWAS studies, Abegaz et al studied the impact of confounding in gene–gene interaction (epistasis) detection.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, intensive research has been underway to identify the causes of CD. Among the numerous approaches that have been taken so far, the unbiased, high-throughput techniques used to analyze DNA, RNA, and proteins are becoming increasingly popular [8][9][10][11][12]. As with any other multifactorial diseases (e.g., cardiovascular disease and diabetes), it is difficult to pinpoint the exact mechanisms underlying CD.…”
Section: Introductionmentioning
confidence: 99%
“…5 In genome-wide association studies to date, more than 120 related genes have been identified for CD, 67 of which were found to be differentially expressed for both CD and UC patients compared to non-IBD individuals. 6 These biological underpinnings have connected IBD to an array of comorbidities including asthma 7 and diabetes, 8 which are also characterized by polygenic architectures and complex environmental interactions related to immune activation. Additionally, many of the genes most strongly associated with IBD diagnosis are active in host-microbe interactions (such as pathogen-associated molecular pattern recognition, inflammatory responses, and phagocytic processes), including toll-like receptor (TLR) 4, TLR9, nucleotide binding oligomerization domain containing 2 (NOD2), interleukin-23 receptor, and tumor necrosis factor.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many of the genes most strongly associated with IBD diagnosis are active in host-microbe interactions (such as pathogen-associated molecular pattern recognition, inflammatory responses, and phagocytic processes), including toll-like receptor (TLR) 4, TLR9, nucleotide binding oligomerization domain containing 2 (NOD2), interleukin-23 receptor, and tumor necrosis factor. 6 Multiple environmental risk factors for IBD have been identified, including smoking, excess body fat, 9 urban living, 10 antibiotic exposure, 10 and adverse childhood events. 11 On the other hand, studies have highlighted protective environmental factors including Helicobacter pylori infection, 12 breastfeeding, 9 and adequate vitamin D status.…”
Section: Introductionmentioning
confidence: 99%